-(7n+6)=5-2(5n-8)

Simple and best practice solution for -(7n+6)=5-2(5n-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(7n+6)=5-2(5n-8) equation:



-(7n+6)=5-2(5n-8)
We move all terms to the left:
-(7n+6)-(5-2(5n-8))=0
We get rid of parentheses
-7n-(5-2(5n-8))-6=0
We calculate terms in parentheses: -(5-2(5n-8)), so:
5-2(5n-8)
determiningTheFunctionDomain -2(5n-8)+5
We multiply parentheses
-10n+16+5
We add all the numbers together, and all the variables
-10n+21
Back to the equation:
-(-10n+21)
We get rid of parentheses
-7n+10n-21-6=0
We add all the numbers together, and all the variables
3n-27=0
We move all terms containing n to the left, all other terms to the right
3n=27
n=27/3
n=9

See similar equations:

| 3b^2+8b-108=0 | | 3w-(-4)=8-1w | | -3(5+7p)=5(-2p+8) | | 331/7=x | | (2y-4)-y=14 | | -16=2(-3x+4 | | 10(-x+8)=20 | | 2(6r-5)+4r=-2(1-2r)-8 | | -4(z-3)=-4 | | 2x-15+2x+20+x=180 | | -22+13=m-1 | | 6x-4)=3x+1 | | 105-25-3b=45-1 | | 10x-(2x=)=-3(15-4x) | | -6n-12=-1-6(n+5) | | -21+24=m-8 | | V-1-6v=2(v+4)-3(8v+3) | | 10=c–2 | | 10-29r+30=40-20r-4r | | x6.2=2.2+x | | 3x+1-2x=4 | | 5n-6(6+2n)=-4(n-1)+2 | | X2+34=10x | | 63*8/x+41=55 | | 0.25(8s-4)=s+8-2s | | 13-2x=-15 | | 14x^2-11x-60=0 | | 3v–1=5 | | 1+2y+7y=19 | | 6x2+7x-20=0 | | 4+a=2a+3 | | 21=6(1-7p)+3(7p+5) |

Equations solver categories